The Implementation of the Outdoor Learning Method to Improve IPAS Learning Outcomes among Fifth-Grade Students at SD Negeri 340 Pantai Timur, Wajo Regency - Sitti Jauhar; Firdaus; Sahri Ramadana (Journal of Primary Education Innovation and Research, 2025)
This study is Classroom Action Research (CAR), which aims to determine how the implementation of the Outdoor Learning method can improve IPAS learning outcomes among fifth-grade students at SD Negeri 340 Pantai Timur. The subjects of this study were all fifth-grade students, totaling 15 students, and the fifth-grade homeroom teacher. The data collection techniques used in this study were observation and tests. The data analysis techniques included data reduction, data presentation, and conclusion drawing. The results showed that the percentage of teacher activity in Cycle I, Meeting I, was 57.14% (Poor), and in Meeting II, it was 61.90% (Fair). In Cycle II, the percentage of teacher activity reached 76.19% (Good) in Meeting I and increased to 90.41% (Good) in Meeting II. The percentage of student activity in Cycle I, Meeting I, was 57.14% (Poor), and in Meeting II, it was 61.90% (Fair). In Cycle II, the percentage of student activity reached 76.19% (Good) in Meeting I and increased to 90.41% (Good) in Meeting II. Students’ learning outcomes also showed a significant improvement. In Cycle I, the students’ mean score was 77, with a learning mastery percentage of 67% (Fair). In Cycle II, the students’ mean score was 84, with a learning mastery percentage of 87% (Good). In conclusion, the Outdoor Learning method can improve IPAS learning outcomes among fifth-grade students at SD Negeri 340 Pantai Timur, Wajo Regency